2000
DOI: 10.1093/oxfordjournals.jbchem.a022610
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a 72-kDa Protein-Tyrosine Kinase from Rat Liver and Its Identification as Syk: Involvement of Syk in Signaling Events of Hepatocytes

Abstract: Syk protein-tyrosine kinase (PTK) has been implicated in a variety of hematopoietic cell responses including immunoreceptor signaling. However, so far, there has been no evidence of the expression of Syk or Syk-related PTK in non-hematopoietic tissues. In this study, we have purified from blood cell-depleted rat liver a 72-kDa cytoplasmic PTK which shows cross-reactivity with anti-Syk antibody. Partial amino acid sequence analysis revealed that this 72-kDa PTK is identical to Syk. Immunohistochemical and RT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 0 publications
0
41
1
2
Order By: Relevance
“…So, it has been suggested that nonhemopoietic cells do not exhibit Syk expression. As this manuscript was being completed, Wang et al (30), using a strategy of reverse transcription and PCR, reported that 3T3-L1 mouse embryonic fibroblasts expressed Syk, and Tsuchida et al (31) reported that hepatocytes expressed Syk. We also found Syk expression in human nasal polyp-derived fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…So, it has been suggested that nonhemopoietic cells do not exhibit Syk expression. As this manuscript was being completed, Wang et al (30), using a strategy of reverse transcription and PCR, reported that 3T3-L1 mouse embryonic fibroblasts expressed Syk, and Tsuchida et al (31) reported that hepatocytes expressed Syk. We also found Syk expression in human nasal polyp-derived fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of phospholipase C␥2 by Syk results in downstream activation of p44/p42 MAPK and JNK kinases (28), whereas PI3K phosphorylation by Syk mediates Akt activity (29). Recent evidence indicates that Syk is also expressed in nonhemopoietic cells, including hepatocytes (30), colon cancer cells (31), and breast cancer cells (32).…”
Section: Tnf Activates Syk Proteinmentioning
confidence: 99%
“…Although cancer-associated CpG island hypermethylation tends to occur in inactive genes in normal cells, 21 SYK methylation develops despite its active expression in normal hepatocytes. 22 Considering that previous studies and the present study have indicated that SYK promoter CpG island hypermethylation is closely associated with poorer prognosis in HCC patients, 10,23 it could be hypothesized that the reduced expression of SYK by promoter CpG island hypermethylation may be related to the biological aggressiveness of HCC.…”
Section: Discussionmentioning
confidence: 69%